Preoperatory treatment of adenocarcinoma of the rectum: historical analysis and correlation between tumor regression grade and the outcomes - Basso, Jeziel; Damin, Daniel de Carvalho; Moreira, Luis Fernando; Lima, Marta Nassif Pereira; Azevedo, Sergio Jobim de; Pereira, Rodrigo Perez (Brazilian Journal of Oncology, 2022)
Introduction: Treatment of locally advanced rectal cancer is based on chemoradiation associated with surgery. Tumor regression grade (TRG) appears to be a prognostic factor and be influenced by the interval between neoadjuvant treatment and surgery.Material and Methods: A retrospective database was formed. We included patients submitted to neoadjuvant chemoradiotherapy and rectal surgery, treated at the Hospital de Clínicas, Porto Alegre. TRG was mensurated by the modified Ryan method, as the American Joint Committee on Cancer (AJCC) suggests. We analyzed outcomes, pathological tumor regression and treatment toxicity data. We also sought to analyze the optimal timing for surgery after chemoradiotherapy, comparing different intervals after chemoradiotherapy with the rate of pCR. Statistical analysis was done with Kaplan Meier, Pearson's chi-square, and the Cox regression method.Results: We accrued 156 patients between 2006 and 2018. The rate of DFS at 3 and 5 years were 75% and 70%, respectively. The 5-year overall survival was 88%. The rate of pCR was 12.8%. TRG 3 was associated with an increase in mortality, HR 3,148 (95%CI: 1.6-12.2, p<0.003) and a decrease in DFS, HR 3,148 (95%CI: 1.7-5.8, p<0.0001). The 5-years DFS with TRG 0,1, 2 and 3 were 95%, 87%, 73.3%, and 48%, respectively. Comparing the interval between the end of radiotherapy treatment and surgery of less than 8 weeks versus 8 and 12 weeks versus above 12 weeks, the rates of pCR were 4.3%, 18.6% and 7.1% and the rates of TRG 3 were 32.6%, 18.6%, and 57,1% (p<0.016), respectively.Conclusion: The outcomes found are favorable. The pathological tumor regression grade is an important prognostic factor. The interval between the neoadjuvant treatment and surgery seems to influence the tumor regression grade, with the best results of surgery observed when performed between 8 and 12 weeks.
Keywords: Rectal neoplasms; Neoadjuvant therapy; Antineoplastic agents; Radiotherapy